BUILDING EMPLOYEE LOYALTY IN THE DIGITAL ERA AND PANDEMIC (STUDY AT THE TECHNICAL IMPLEMENTATION UNIT OF THE SOUTH SULAWESI PROVINCE FOOD CROPS AND HORTICULTURE PROTECTION AGENCY) - Heru Setyoko; Sri Widyastuti; Edie Toet Hendratno (International Journal of Social Science, 2023)
Organizational phenomena that are still being faced are coordination and consolidation, different qualifications of human resources, large work areas, and the lack of facilities (technology) and assistance facilities for the community. The purpose of this study was conducted to develop variables that influence Loyalty in the Digital Age and the COVID-19 Pandemic, in the Observers of Plant Pest Organisms (POPT) in South Sulawesi Province. The research method uses the Mix Method to determine the relationships and influences between variables, with 200 respondents. Selection of the sample using judgment sampling and data collection using a questionnaire. Data is processed using Structural Equation Modeling (SEM) using LISREL and SPSS. The results showed that the Human Resource Management variable had the most influence on building loyalty. Overall the variables of Human Resource Management Practices, Motivation, Communication, have a positive and significant effect on Job Satisfaction, but the variable that has the greatest influence on job satisfaction is the communication variable. Meanwhile, the stress variable has a negative effect on job satisfaction